Behaviour of Sandwiched Concrete Beam under Flexural Loading - . Firdaus; . Rosidawani (Bandar Lampung University (UBL), 2012)
Beam is an structural element whose main function to carry external load in the direction perpendicular to the axis of the beam. Theoretically, it is assumed when the concrete starts to crack the tension in the concrete can be neglected. Bending moment at the cross section at the location of the crack is carried by a pair of coupled forces; compressive force happens in the compressive zone above the neutral line and the tension force happens in the tension zone below the neutral line. In this kind of flexural respons, it seems that the middle part of the cross section in the vicinity of the neutral line does not have to carry any stress. This Fact gives the idea to combine normal concrete and light weight concrete in a sandwich structure.The main intention of this investigation is to conduct an experimental study on the flexural behavior of three layer concrete sandwich beam. The central layer is made of light weight concrete with compressive strength of 30 MPa. The center layer is sandwiched between two outer layer made of normal concrete with compressive strength 50 MPa. The test was conducted on four beams speciments with dimensions of 2100 mm in length, 100 mm width and depth of 200 mm. Flexural beam subjected to static and cyclic load. Observation on load-deflection curves show that flexural strength capacity is determined by the loading systems, the contact conditions of the interfaces in composite system due to the use and the material properties of connectors in the middle part of the concrete beams.